Purification, Structural Analysis and Bioactivity of Pueraria montana Polysaccharide - Dandan Chen; Hongliang Yao; Xiang Qiu; Lang Xu; Yanghui Ou; Jianghui Xin; Shengjia Lu; Mengjie Li; Yan Geng; Yali Zhang; Minxiu Hu; Zhiming Ren; et al. (Foods)
Pueraria montana is a medicinal and edible plant widely distributed in Asia. It has antipyretic, analgesic, and anti-inflammatory properties. In this study, a novel polysaccharide (PMPS-A1) was obtained through purification, and its biological activity was investigated. Structural analysis revealed that PMPS-A1 was composed of fructose and glucose, with a molecular weight of 12168 Da. The main chain structure was →1)-β-D-Fruf-(2→, →4)-α-D-Glcp-(1→, →4)-α-D-Glcp-(1→, and →4)-α-D-Glcp-(1→. The branched chain of α-D-Glcp-(1→3)-α-D-Glcp-(1→ and α-D-Glcp-(1→ connected to the O-3 and O-6 positions of residue →3,4)-α-D-Glcp-(1→ and →4,6)-α-D-Glcp-(1→, respectively. In vitro, PMPS-A1 had a favorable scavenging ability of the hydroxyl radical and 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical and downregulated the expression of interleukin-6 and nitric oxide in lipopolysaccharide-induced RAW264.7 macrophages. In addition, the Caenorhabditis model assay demonstrated that PMPS-A1 decreased the buildup of lipofuscin and reactive oxygen species. Overall, these results enhance our knowledge of the chemical composition and bioactivity of a Pueraria montana polysaccharide and point to the potential use of PMPS-A1 for antioxidant and anti-aging qualities, providing a theoretical basis for the medicinal and edible application of Pueraria montana polysaccharide.